1989
DOI: 10.1152/jappl.1989.67.5.1740
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the febrile responses of rats to endogenous pyrogen occurs within the OVLT region

Abstract: The febrile responses of male Sprague-Dawley rats to a semi-purified endogenous pyrogen (EP) derived from human monocytes are markedly enhanced 3 days after the animals are intravenously injected with a variety of immunoadjuvants. The present study was designed to investigate the site within the body at which these substances act to produce this febrile-enhancing phenomenon. Stainless steel microinjection cannula guide tubes were implanted within the region of the organum vasculosum lamina terminalis (OVLT) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Moreover, expression of TLR2 and TLR6 was reported in endothelial cells of the CNS, and zym was associated with an increase in the permeability of the vessels by damage of the intercellular junctions (44). In addition, as mentioned earlier, zym injected into the OVLT potentiated EP-induced fever (70). Altogether, these studies indicated that zym could also have a direct effect on the CNS, particularly in areas related to fever.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, expression of TLR2 and TLR6 was reported in endothelial cells of the CNS, and zym was associated with an increase in the permeability of the vessels by damage of the intercellular junctions (44). In addition, as mentioned earlier, zym injected into the OVLT potentiated EP-induced fever (70). Altogether, these studies indicated that zym could also have a direct effect on the CNS, particularly in areas related to fever.…”
Section: Discussionsupporting
confidence: 59%
“…We further investigated whether zym could activate important regions related to the febrile response; namely, the OVLT [as suggested in Ref. (70)] and median preoptic nucleus (MnPO), a major preoptic site involved in thermoregulation (45,64,75).…”
mentioning
confidence: 99%
“…Therefore, the hypothalamic region seems to be endowed with all the functional requirements needed for local formation and action of endothelins. However, one cannot discard the possibility that endothelins formed in the periphery may reach the hypothalamus via the organum vasculosum laminae terminalis (OVLT, as indeed do several cytokines; Stitt & Shimada, 1989), or that cytokines acting on endothelial cells of this structure stimulate endothelin formation. Whatever the source of endothelins mobilized by LPS to cause fever, it is noteworthy that bosentan and BQ‐788 only inhibited this response significantly from 2.5 h onwards, a finding consistent with the slow onset of temperature changes induced by i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that an initial muscle injury might also "sensitize" the body so that a second set of muscular injuries would accentuate adverse thermoregulatory responses. It has been demonstrated that immunoadjuvant exposure 3 days before introduction of endogenous pyrogen will enhance the febrile response to pyrogen exposure (22,23). Because tissue injury can produce an acute inflammatory response and secretion of cytokines (2,3,6,16), it is possible that muscle or other tissue injury (i.e., gut, endothelial) produced by prior exercise could serve as the priming mechanism to sensitize the brain receptor sites to subsequent cytokine exposure and alter the thermoregulatory responses to exercise-heat stress.…”
mentioning
confidence: 99%